Signaling pathway of targeting the pancreas in the treatment of diabetes under the precision medicine big data evaluation system - Song, Ge; Zhang, Yiqian; Jiang, Yihua; Zhang, Huan; Gu, Wen; Xu, Xiu; Yao, Jing; Chen, Zhengfang (Frontiers in Genetics, 2023)
Diabetes is a chronic noncommunicable disease, which is related to lifestyle, environmental and other factors. The main disease of diabetes is the pancreas. Inflammation, oxidative stress and other factors can interfere with the conduction of various cell signaling pathways, thus inducing pancreatic tissue lesions and diabetes. Precision medicine covers epidemiology, preventive medicine, rehabilitation medicine and clinical medicine. On the basis of precision medicine big data analysis, this paper takes pancreas as the target to analyze the signal pathway of diabetes treatment. This paper analyzes from the five aspects of the age structure of diabetes, the blood sugar control standard of type 2 elderly diabetes mellitus, the changes in the number of diabetic patients, the ratio of patients using pancreatic species and the changes in blood sugar using the pancreas. The results of the study showed that targeted pancreatic therapy for diabetes reduced the diabetic blood glucose rate by approximately 6.94%.